Teaching English to Young Learners: More Teacher Education and More Children's Literature! - Janice Bland (CLELEjournal, 2019)
In Janice Bland's paper, the availability of focused pre-service and in-service teacher education, as well as teacher educators with the necessary expertise, is discussed. The role of children's literature in teacher education is highlighted and the relevance of high-quality language input is foregrounded.